Mengimplementasikan Nilai Keadilan dalam Pengaruh Era Globalisasi Masyarakat untuk Menuju Indonesia Emas - Candrika Linda Ayu Kusumaningrum; Edy Soesanto; Ahmad Maulana Razanny Putra (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
The development of the era of globalization has also had an important influence on all areas of people's lives, including the values ​​of justice which are the main basis for achieving social harmony. This research aims to analyze how the value of justice is applied in facing the effects of globalization. The focus of the research is on the efforts made to build an Indonesian society that has the ability to compete, is inclusive, and has values ​​of justice as a step towards the vision of a Golden Indonesia 2045. A qualitative approach has been used by analyzing literature and empirical insights related to social justice practices in various sectors, such as economics, education and politics. The research results note that to increase the value of justice, harmonious cooperation between government policies, public awareness and active involvement of various interested parties is needed. The values ​​of justice can be realized through increasing access to education, leveling the economy, and implementing the law transparently. Apart from that, the era of globalization also provides an opportunity to take best practices from various countries in realizing social justice, as long as they are adapted to the cultural context and needs of Indonesian society. The research results show that it is important to apply the values ​​of justice consistently and adaptively as the main step in overcoming various problems faced in the era of globalization and ensuring a sustainable development journey in order to realize a Golden Indonesia. Strategic suggestions include improving regulations, better understanding of society, and developing inclusive programs that are based on the principles of social justice. The main focus of the discussion is on justice, globalization, the role of society in realizing a Golden Indonesia, and sustainable development efforts.